STUDI KUALITAS REPAIR WELDING MENGGUNAKAN METODE OXY-ACETYLENE DENGAN PWHT PADA CAST WHEEL ALUMINIUM - Wilopo, Irman Azis (Jurnal Nosel, 2014)
The purposes of this research are: (1) To determine the chemical composition and aluminum alloy standard codification of cast wheel aluminum. (2) To determine the microstructure before and after welding with oxy - acetylene welding method with PWHT on the cast aluminum wheel. (3) To determine the level of hardness and level of impact strength before and after welding with oxy - acetylene welding method with PWHT on the cast wheel aluminum. The research was conducted in the laboratory INLASTEK Surakarta. The Object in this research used are aluminium cast wheels. Techniques of data analysis in this research using descriptive data analysis that is directly observed  experimental results and then analyzed and summing up the results of the research. As an input parameter in analyzing the data include:the testing of chemical composition, microstructure, hardness and impact. From  the research, we can conclude that  the  chemical composition on  aluminium  cast wheel including Aluminium  Silicon alloy,  because the element  Si alloy is the largest with 4.61% Si. Microstructure on  base metal granules the spread equally on the surface of  Al. Specimen hardness value of raw material is higher than oxy-acetylene welding specimens. The average value of raw material hardness results 42.69 BHN while the average value of oxy-acetylene  welding results 34.34 BHN. Average hardness oxy-acetylene welding specimens in the HAZ area 31.81 BHN. The average value of raw material impact results 0,092 J/mm² while the average value of oxy-acetylene welding results 0,078 J/mm². Post-weld heat treatment (PWHT) was effect on the mechanical properties and microstructural that characterized by nearly changes in the microstructure between the weld region, HAZ , and base material after PWHT process .